Impact of Short Bowel Syndrome on Quality of Life and Family: The Patient's Perspective - Pederiva, Federica; Khalil, Basem; Morabito, Antonino; Wood, Sarah J. (European Journal of Pediatric Surgery, 2019)
Background Short bowel syndrome (SBS) has an impact on children and their families not only physically, but also emotionally, mentally, and socially. This study aimed to evaluate quality of life and family impact in patients with SBS, using the Pediatric Quality of Life Inventory (PedsQL) measurement model.Materials and Methods PedsQL questionnaires were administered to patients with SBS followed at the Pediatric Surgery of Royal Manchester Children's Hospital. The scores were compared between two groups differing in age (children <5 y vs. >5 y) and with known-groups from literature published by Varni et al.Results Forty-three patients were sent the questionnaires, and 30 (70%, 17 < 5 and 13 > 5) responded. Family Impact Module failed to distinguish between families of children younger and older than 5 years of age. In contrast, it distinguished between families with SBS children and the ones with children in a long-term care facility. Healthcare satisfaction was worse in families of children over 5 years regarding information received, inclusion of the family, and communication. When compared with normal population, SBS children scored worse on Generic Core Scales for all domains except for emotional functioning.Conclusion Although advances have been made on the treatment of children with SBS, and improvements have been reached on home PN, this condition is still significantly affecting the quality of life of children and their families. The future quality control of medical care must have greater focus on psychosocial and emotional functioning, aiming for the best possible quality of life.
Keywords: short bowel syndrome; health-related quality of life; Pediatric Quality of Life Inventory